2021
DOI: 10.1111/eci.13588
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between gut microbiota, bone health and vascular calcification in chronic kidney disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 148 publications
1
13
0
Order By: Relevance
“…SCFAs may have immunomodulatory effects. Inflammatory cells, such as neutrophils, macrophages, dendritic cells, and T cells are responsive to SCFA treatment, which is consistent with the anti-inflammatory role of SCFAs in a wide range of inflammatory diseases and the reduction of VC [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…SCFAs may have immunomodulatory effects. Inflammatory cells, such as neutrophils, macrophages, dendritic cells, and T cells are responsive to SCFA treatment, which is consistent with the anti-inflammatory role of SCFAs in a wide range of inflammatory diseases and the reduction of VC [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 63%
“…Ruminococcus are gram-positive anaerobic bacteria belonging to the family Ruminococcaceae and the phylum Firmicutes, which are widely recognized for their capacity to hydrolyze and ferment many structural and storage polysaccharides to produce short-chain fatty acids (SCFAs), such as butyrate [ 28 , 29 ]. Recent studies found that SCFAs seem to contribute to the improvement of vascular phenotypes [ 1 , 30 ]. SCFAs may have immunomodulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the mineral bone disorder associated with CKD is characterised by one or more abnormalities in circulating minerals and their regulating hormones, bone abnormalities, and VC [ 21 ]. Mounting evidence indicates that the gut dysbiosis associated with CKD may be involved in the pathogenesis of bone–vascular axis [ 8 , 23 ]. Recent data suggest that an increased protein fermentation, and consequent uremic toxins production, decreased carbohydrate fermentation, vitamin K deficiency, and gut-derived inflammation may, alone or together, drive to a vascular and skeletal pathobiology in CKD patients [ 8 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence indicates that the gut dysbiosis associated with CKD may be involved in the pathogenesis of bone–vascular axis [ 8 , 23 ]. Recent data suggest that an increased protein fermentation, and consequent uremic toxins production, decreased carbohydrate fermentation, vitamin K deficiency, and gut-derived inflammation may, alone or together, drive to a vascular and skeletal pathobiology in CKD patients [ 8 , 23 ]. Still, to our knowledge, there are currently no data on the putative association between blood microbiome and vascular calcification.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome may act as a bridge between kidneys, aging and IS disorders ( 9 ). Microbiota evolves normally from newborn to elderly, as a result of epigenetic mechanisms, environmental factors, personal habits, nutrition, etc.…”
mentioning
confidence: 99%